The Role of Cultural Values in Feeding Practices among Children with Stunting in Jembrana Regency: A Qualitative Approach - Agustina, Komang Srititin; Kesumawati, Ketut Anom Sri (Babali Nursing Research, 2025)
Introduction: Stunting remains a public health problem in Jembrana Regency, Bali. Despite a decline in prevalence, persistent cases suggest that cultural and nutritional factors influence feeding practices. This study aimed to explore cultural meanings and practices shaping feeding behaviors among children with stunting. Methods:  This study employed a qualitative approach with an ethnographic design. The subjects of this study were 10 mothers or caregivers of children aged 12 - 59 months with stunting, residing in Jembrana Regency, and one healthcare worker was selected using a purposive sampling technique. Data were collected through an in-depth interview guide, an observation sheet, documentation, and field notes. The collected data were then analyzed using a thematic analysis approach. Data validity was ensured through triangulation, peer debriefing, and member checking.          Results: The study identified four main themes that reflect how cultural values shape feeding behaviors in children with stunting. These themes include: (1) Snacks as substitutes that reduce appetite for main meals; (2) Normalization of small body size; (3) Flexibility expressed as "as long as the child wants to eat"; and (4) Collective caregiving culture (allomothering). Conclusion: Stunting in Jembrana is influenced by cultural values and family dynamics, so effective interventions must be culturally sensitive and target snack habits, parental misconceptions, dietary diversity, and caregiving coordination, including the role of grandmothers, to reduce stunting risk. Providing culturally sensitive nutrition education involving extended family and child caregivers is necessary in nursing.